Neutrophil-induced pyroptosis promotes survival in patients with hepatoblastoma - Tingyi Fu; Jiquan Zhou; Liyuan Yang; Jing Wang; Hui Li; Yuhua Shan; Hongxiang Gao; Chenjie Xie; Dapeng Jiang; Lei Zhang; Ji Ma; Qiuhui Pan; et al. (Cancer Immunology, Immunotherapy)
Abstract Background Hepatoblastoma (HB) is the predominant hepatic malignancy among children. Despite therapeutic options for HB were gradually refined in recent years, patients with metastasis suffer from an unsatisfactory prognosis. Pyroptosis is a type of programmed and inflammatory necrosis. Neutrophils are crucial in innate immunity, which were shown to be associated with tumor progression. Our study strived to unravel the relationship between neutrophil-induced pyroptosis (NIP) and HB. Methods The clinical and bulk RNA sequencing data of 38 patients with HB were obtained from Shanghai Children’s Medical Center. We established NIP score based on the LASSO regression. The single-cell RNA sequencing data (GSE186975) were used for for key genes identification, cellular communication, and differentiation trajectories of neutrophils. KEGG, GO, GSVA, and ssGSEA enrichment were used to analyze biological functions, including neutrophil extracellular traps (NETs), NOD-like receptors pathway, neutrophil activation, neutrophil-mediated cytotoxicity, and others. Results We constructed a NIP score based on the expression of three genes related to neutrophil and pyroptosis, namely ELANE, CASP1, and NOD2, which was positively correlated with a favorable prognosis of HB. Moreover, we clarified the function of ELANE in HB microenvironmwnt. Immunohistochemistry and transcriptome analysis unraveled a significant correlation between NETs and pyroptosis in HB, suggesting the key role of NETs-related neutrophils in inducing pyroptosis and prolonging survival. We also found upregulated tumor-promoting and immunosuppression-related pathways in the HB microenvironment. In addition, we clarified the growth trajectories and phenotypic changes of neutrophils in the immune microenvironment of HB, which can serve as potential targets for immunotherapy. Conclusions The novel NIP score for patients with HB shows high predictive value for survival. Moreover, we identified biological function, cellular communication, and growth trajectories of neutrophils in HB. Our findings broaden insights into the treatment of HB.